2015
DOI: 10.3109/10715762.2015.1099642
|View full text |Cite
|
Sign up to set email alerts
|

Liver ergothioneine accumulation in a guinea pig model of non-alcoholic fatty liver disease. A possible mechanism of defence?

Abstract: L-ergothioneine (ET), a putative antioxidant compound acquired by animals through dietary sources, has been suggested to accumulate in certain cells and tissues in the body that are predisposed to high oxidative stress. In the present study, we identified an elevation of ET in the liver of a guinea pig model of non-alcoholic fatty liver disease (NAFLD), elucidated a possible mechanism for the increased uptake and investigated the possible role for this accumulation. This increase in liver ET levels correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 66 publications
5
54
0
Order By: Relevance
“…Some studies have presented evidence that ET may be accumulated at sites of tissue injury, in particular in fatty liver disease, liver fibrosis, pressure overloaded and infarcted hearts and pre-eclampsia. This accumulation seems to relate to an increased expression of the gene encoding OCTN1, resulting in increased transporter activity [46][47][48][49]. We have suggested [46,50] that this is a deliberate cytoprotective mechanism (Fig.…”
Section: An "Adaptive" Antioxidant?mentioning
confidence: 90%
“…Some studies have presented evidence that ET may be accumulated at sites of tissue injury, in particular in fatty liver disease, liver fibrosis, pressure overloaded and infarcted hearts and pre-eclampsia. This accumulation seems to relate to an increased expression of the gene encoding OCTN1, resulting in increased transporter activity [46][47][48][49]. We have suggested [46,50] that this is a deliberate cytoprotective mechanism (Fig.…”
Section: An "Adaptive" Antioxidant?mentioning
confidence: 90%
“…ERG has been shown to decrease oxidative stress in the liver and kidney of rats (469) , rescued cells from β-amyloid-induced apoptotic death (231) , protected against palmitic acid-induced cell death (470) , mercuric chloride-induced cellular dysfunction (471) , and prevented Cu-induced oxidative damage to DNA (472,473) . It is protective against the oxidation of various kinds of molecule (251,474) , including astaxanthin (475) , and accumulates in a guinea-pig model of non-alcoholic fatty liver disease (476) , massively so in mouse models of myocardial infarction and heart failure (477) , and in a rat model of optic nerve crush (478) . It serves to resist H 2 O 2 -induced cell death (479) , pyrogallolinduced toxicity (124) , cisplatin- (480) or oxaliplatin-induced (481) toxicity, glucose-induced senescence (246,482) , as well as lipopolysaccharide-induced inflammation (483) .…”
Section: The Biology Of Ergothioneinementioning
confidence: 99%
“…We have also identified the presence of ET in post-mortem human brain and cerebrospinal fluid (unpublished data). Moreover, evidence suggests that that tissues may increase ET uptake (by elevating expression of its transporter, OCTN1) in response to disease or tissue injury, to possibly mitigate further oxidative damage [26,64]. In addition to alleviating Ab oligomer-mediated toxicity as demonstrated in this study, ET has also been demonstrated to function as an antioxidant [23,24], chelate metal ions [58,60], modulate inflammation [65,66], accumulate in mitochondria and protect against mitochondrial dysfunction [67,68] and prevent NMDA excitotoxicity-induced neuronal death in rat retinal neurons [29].…”
Section: Ergothioneine a Viable Therapeutic For Neurodegeneration?mentioning
confidence: 99%